Interação de herbicidas empregados na cultura do arroz irrigado para o controle de arroz daninho e angiquinho - Silva, Renan Souza (2017)
Irrigated rice (Oryza sativa) is a crop that feeds billions of people worldwide, with record-breaking yields. However, weeds still represent problems for rice to express its productive potential, especially weedy-rice, of the same species as the cultivated one. Last years, with Clearfield® (CL) technology, many producers have taken a technology as a solution of the weedy-rice problems. However, the possibility of gene flow of CL rice to a weed brought problems with a technology. A new strain of rice, which uses another mode of action of herbicides (inhibitors of ACCase), this time, is about to be launched in the market and aims to be a new tool in the process of combating weedyrice. Allied to this tool, there is a point of increase without control of weed control of the rice with the advent and a legalization of the association of herbicides in the country. For this it is necessary to know the effects of the associated products and a selectivity of the rice in front of the associations, since there is a possibility of synergistic or antagonic interactions in the association of latifolicides with herbicides of this mechanism of action. Although not a legal practice, the association of herbicides is one more alternative for the rice producers in the fight against the problems with resistance of weeds. The objectives of this study were: to carry out a literature review about the mode of action of the herbicides registered for rice and the interaction effects caused by the interaction of herbicides (Chapter I); To elucidate the interactions resulting from the association between quizalofop and haloxyfop with herbicides registered for rice (Chapter II); And to study the effects on rice of two strains (susceptible and resistant to ACCase inhibitors) subject to the application of supposedly antagonistic herbicides (Chapter III). The results indicate that rice control efficiency was reduced with all doses evaluated in most associations of quizalofop and haloxyfop. There was supposed antagonism or additive effect on the associations of quizalofop with all products at all doses in Aeschynomene denticulata. Other studies should be performed using dose response curves and isobolograms assembly to prove the assumption of the interaction verified. The results evidenced the supposed antagonistic interaction between 2,4-D and quizalofop and between quizalofop and propanil in the three studied biotypes.